Intraoperative determination of coupling efficiency of Carina® middle ear implant by means of auditory evoked potentials. (1st December 2020) - Cebulla, Mario; Hagen, Rudolf; Rak, Kristen; Geiger, Ute
Abstract: Objective: The Carina ® implant system is a fully implantable active middle ear implant, which can be coupled to various structures in the middle ear, depending on the nature of the hearing loss and the middle ear anatomy. Currently, there is only one method for determining the coupling efficiency of the actuator of this implant system, and this is limited to incus coupling. Design: The proposed method is based on the intraoperative recording and evaluation of auditory brainstem responses (ABRs) while directly stimulating the hearing system via the actuator. The acoustic stimulation was achieved using an optimised broadband chirp stimulus (CE-Chirp ® ). Study samples: This study included 10 subjects having moderate to severe sensorineural or mixed hearing loss. Results: The intraoperative ABR measurements show, that it is possible to derive reliable AEP thresholds via the actuator of the implant. The ABR thresholds correlate well with preoperative BC PTA4 thresholds (r = 0.87) while the postoperative OC-direct thresholds (in situ audiogram via the implant) correlate with r = 0.77. Conclusion: The results demonstrated that the direct actuator stimulation allow for reliable intraoperative ABR measurements and that the proposed method can be used to estimate the coupling efficiency of the actuator and facilitate its positioning.